Ilmu Ushuluddin dan Issue Strategis di Aceh - Syamsul Rijal (Ar-Raniry: International Journal of Islamic Studies, 2014)
Memorandum of Understanding (MoU) forecloses the intellectual attention and scientific challenges that are able to provide a positive solution in dynamic changes. Islamic application law on ”dejure and defacto” as well as challenges that actually require the application of thought in law that is more dynamic and solution adaptiveresponding to the up to date issues, and in turn there will be the suit to the existence and provide the chance of theology and challenges of dynamic changing of how it should be in the development og theology. The faculty of theology can be a strategic role as a cornerstone institution development is surrounded by the researchers qualified as the agent of change to the human life.